(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2024)
Loyalty towards an organization determines its growth and furthers the possibilities of being a successful organization. Banking services are entirely dependent on the user’s satisfaction and user loyalty. The purpose of this research is to measure the impact of user’s satisfaction on user’s loyalty of India Post Payment Bank. The technique used for the current study is structural equation model using SMART PLS. According to the study’s findings, customer satisfaction appears to have a favourable, considerable influence on customer loyalty.